Pengaruh Pelatihan Kerja, Komunikasi, Dan Kepuasan Kerja Terhadap Kinerja Karyawan Pada PT. Kurnia Anggun II Mojokerto - Silvia Masrurotin; Hadi Sunaryo; Mohammad Rizal (E-JRM : Elektronik Jurnal Riset Manajemen, 2021)
Abstrack This study was conducted to determine the effect of job training, communication, and job satisfaction on employee performance at PT. Kurnia Anggun II Mojokerto.The sample used in this study were 62 production employees of the section  packing who were contract employees. The data analysis method used in this research is quantitative data analysis using descriptive statistical analysis and inferential statistics. Data analysis techniques used in this study include instrument testing, normality test, multiple linear regression, classical assumption test, hypothesis testing and coefficient of determination using SPSS 25.The results of the descriptive analysis in this study indicate that the employees of PT. Kurnia Anggun II Mojokerto agrees with all research variables, namely job training, communication, job satisfaction, and employee performance. The results of this study indicate that vocational training has an impact on employee performance. Communication affects employee performance. Job satisfaction affects employee performance. Job Training, Communication, and job satisfaction simultaneously affect the performance of employee of PT. Kurnia Anggun II Mojokerto. Keywords: Job Training, Communication, Job Satisfaction, and Employee Performance